Relationship between learning strategies and motivation by using structural equation modeling approach - Mohamed Adnan, Mohamad Azrien; Nordin, Mohamad Sahari; Ibrahim, Mohd Burhan (MOJES, 2013)
This paper aimed at examining the learning strategies constructs and to investigate the relationship between learning strategies and motivation in Arabic courses. The study uses a questionnaire as the information-gathering instrument, and the participants comprised students from two public universities in Peninsular Malaysia who are studying Arabic language. A total of 139 students were selected for this study. The questionnaire’s construct validity was tested using confirmatory factor analysis. Confirmatory factor analysis indicated that a model including factors representing the dimensions metacognitive self-regulation, organization and peer learning was the best fit. Significant correlations between motivation and learning strategies subscales (metacognitive self-regulation and organization) provided preliminary evidence of predictive validity of the measure. Metacognitive self-regulation strategy has positive correlation with organization and peer learning strategy. The organization strategy was also positively correlated to peer learning strategy. The metacognitive self-regulation and organization have significant effect on motivation. Contrary to our expectation, peer learning has no significant effect on motivation.